Perceptions of Democracy and Trust in the Criminal Justice System: A Comparison Between Mainland China and Taiwan. (June 2015) - Hsieh, Ming-Li; Boateng, Francis D.
For more than 50 years, research has been accumulating on how regime differences impact Mainland China and Taiwan in terms of socioeconomic transformation, the development of politics and constitutions, and diverse issues of foreign policy. Much less is known, however, about differences in public confidence in the criminal justice system. To address the obvious gap, this study utilized second-wave data collected by the Asian Barometer cross-national survey. Findings demonstrated that Chinese citizens reflect higher levels of trust in criminal justice institutions than their Taiwanese counterparts and public perceptions of the degree of democracy had a positive effect on public attitudes. Citizens who acknowledge more satisfaction with institutional performance also tend to have more trust in the criminal justice system.